Analysis of Social Domination and Alienation: A Critical Reading of Gregor Samsa in Franz Kafka’s The Metamorphosis within the Context of Modern Power Relations - Biruni, Muhamad Mazeinda Al; Syihabuddin, Syihabuddin (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2025)
This study aims to analyze the practices of social domination and the experiences of alienation encountered by Gregor Samsa in Franz Kafka’s The Metamorphosis through the integration of Seeman’s Alienation Theory and Pratto’s Social Dominance Theory. This investigation emerges from the need to understand how power relations within the family sphere and pressures from the capitalist work system shape conditions of estrangement that erode an individual’s identity, dignity, and social relations. The research employs a qualitative approach using close reading techniques applied to the literary text. The analysis is strengthened by Abrams’s model, which emphasizes the relationship between text, reader, and contemporary social context, thereby enabling a more interdisciplinary interpretation. The findings reveal that Gregor experiences the five forms of alienation identified by Seeman—powerlessness, meaninglessness, social isolation, self-estrangement, and anomie. These forms of alienation emerge as direct consequences of the family’s structure of domination, led by the father and reproduced by Grete, and are further reinforced by pressures from the capitalist economic system that reduces Gregor to an instrument of production. The results demonstrate that social domination operates not only through physical and symbolic power but also through internalization processes that lead Gregor to accept himself as “the other,” ultimately causing the loss of his identity and the meaning of his existence. This study offers an original contribution by addressing a gap in the literature through the integration of Seeman’s and Pratto’s theoretical frameworks—a combination rarely applied in Kafka studies—to show that alienation cannot be understood solely as a psychological phenomenon but must be viewed as the outcome of structural power relations within the family. The study also affirms that literary works can serve as reflective media for examining the dynamics of domination, structural violence, and the erosion of human dignity in contemporary social realities.